The Study of the Reaction of Morpholine with 4-Bromobenzaldehyde in the Presence and Absence of Copper(I) Iodide - Sivasubramaniam, Dorairaaj; Tay, Meng Guan (Borneo Journal of Resource Science and Technology, 2016)
This short communication reports the comparison of the reaction between morpholine with 4- bromobenzaldehyde in the condition with and without copper (I) iodide (CuI) as the catalyst. The reactions were carried out at 110 ºC under reflux condition for 24 hours, and the products were analysed using gas chromatography mass spectroscopy (GCMS). The GC results showed that the conversion of the product without CuI catalyst was higher than the reaction with catalyst under the same condition. Side product also was observed in the reaction without catalyst, which is because the morpholine was actually also attacked to the carbon in the carbonyl group of 4-bromobenzaldehyde to produce 4-bromobenzoic acid morpholide.